Performance Assessment and Chip Morphology Evaluation of Austenitic Stainless Steel under Sustainable Machining Conditions - Anshuman Das; Smita Padhan; Sudhansu Ranjan Das; Mohammad S. Alsoufi; Ahmed Mohamed Mahmoud Ibrahim; Ammar Elsheikh (Metals, 2021)
Sustainable manufacturing has received great attention in the last few decades for obtaining high quality products with minimal costs and minimal negative impacts on environment. Sustainable machining is one of the main sustainable manufacturing branches, which is concerned with improving environmental conditions, reducing power consumption, and minimizing machining costs. In the current study, the performance of three sustainable machining techniques, namely dry, compressed air cooling, and minimum quantity lubrication, is compared with conventional flood machining during the turning of austenitic stainless steel (Nitronic 60). This alloy is widely used in aerospace engine components, medical applications, gas power industries, and nuclear power systems due to its superior mechanical and thermal properties. Machining was performed using SiAlON ceramic tool with four different cutting speeds, feeds and a constant depth of cut. Consequently, various chip characteristics such as chip morphology, chip thickness, saw tooth distance and chip segmentation frequency were analyzed with both optical and scanning electron microscopes. Performance assessment was performed under the investigated cutting conditions. Our results show that the tool life under MQL machining are 138%, 72%, and 11% greater than dry, compressed air, and flooded conditions, respectively. The use of SiAlON ceramic tool results is more economically viable under the MQL environment as the overall machining cost per component is lower ($0.27) as compared to dry ($0.36), compressed air ($0.31), and flooded ($0.29) machining conditions. The minimum quantity lubrication technique outperformed the other investigated techniques in terms of eco-friendly aspects, economic feasibility, and technical viability to improve sustainability.